Inter- and Intraspecific Trait Compensation of Behavioural and Morphological Defences in a Damselfly Genus - Mühlenhaupt, Max; Jiang, Bin; Brauner, Oliver; Mikolajewski, Dirk J. (Frontiers in Ecology and Evolution, 2022)
Predation is a key driver of phenotypic diversification with prey having evolved sets of correlated anti-predator traits. Changes in anti-predator traits can be studied on an evolutionary as well as on a developmental timescale. Using a common garden setup, we studied inter- and intraspecific correlations of behavioural and morphological defences in four damselfly species that either occur in habitats dominated by predatory fish (fish habitats) or fishless habitats by raising larvae either with predatory fish or in a control treatment. We found inter- as well as intraspecific trait compensation (negative correlations) between behavioural and morphological defences. Compared to fishless habitat species, fish habitat species invested more in behavioural defences and less in morphological defences. This was mirrored by fish habitat species investing more in behavioural defences and less in morphological defences when reared with predatory fish whereas fishless habitat species invested less in morphological defences only. Our results emphasize the role of context-specific combinations of defensive traits to avoid predation. We suggest, considering changes in multiple correlated traits on different timescales when studying the evolution of anti-predator traits.